Chemically modified and conjugated antimicrobial peptides against superbugs. (12th March 2021) - Li, Wenyi; Separovic, Frances; O'Brien-Simpson, Neil M.; Wade, John D.
Abstract : Chemical modification of antimicrobial peptides augments their antibacterial action via multiple mechanisms. Abstract : Antimicrobial resistance (AMR) is one of the greatest threats to human health that, by 2050, will lead to more deaths from bacterial infections than cancer. New antimicrobial agents, both broad-spectrum and selective, that do not induce AMR are urgently required. Antimicrobial peptides (AMPs) are a novel class of alternatives that possess potent activity against a wide range of Gram-negative and positive bacteria with little or no capacity to induce AMR. This has stimulated substantial chemical development of novel peptide-based antibiotics possessing improved therapeutic index. This review summarises recent synthetic efforts and their impact on analogue design as well as their various applications in AMP development. It includes modifications that have been reported to enhance antimicrobial activity including lipidation, glycosylation and multimerization through to the broad application of novel bio-orthogonal chemistry, as well as perspectives on the direction of future research. The subject area is primarily the development of next-generation antimicrobial agents through selective, rational chemical modification of AMPs. The review further serves as a guide toward the most promising directions in this field to stimulate broad scientific attention, and will lead to new, effective and selective solutions for the several biomedical challenges to which antimicrobial peptidomimetics are being applied.